ANALYSIS OF PERITONEAL FLUID CYTOLOGY: CORRELATIONS WITH CLINICAL AND BIOCHEMICAL FINDINGS - Sonali Bandil; Anish Kumar; Garima Singh; Shubhangee Arya; Naushad Hussian (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: The analysis of peritoneal fluid, obtained through paracentesis, provides valuable insights into the pathological processes occurring within the peritoneal cavity. The correlation between cytological findings and clinical as well as biochemical parameters is crucial for accurate diagnosis and management of abdominal diseases. Studies have shown that the cytological analysis of peritoneal fluid can offer significant prognostic and diagnostic information, particularly in cases of abdominal cancers such as ovarian and gastric cancer. Materials & Methods: This prospective study was conducted at a teaching hospital in Firozabad over a period of one and a half years, from Feb. 2022 to August 2024. A total of 60 cases involving ascitic fluids using purposive sampling were included in the study. Ascitic fluid was obtained through paracentesis and collected in sterile containers for analysis. Fluid samples were subjected to routine analysis including total white blood cell (WBC) and red blood cell (RBC) counts using Neubauer’s chamber, Sediment from the fluid was prepared and examined microscopically. Results: Majority of the cases were males (76.6%) while females were (23.4%). majority of the cases were in the age group of 41-50 years followed by 1-40 years Liver cirrhosis was found to be the most common cause of Ascitic fluid (51.6%) followed by Anemia- Hypoproteinemia (15%) followed by Nephrotic Syndrome (10%). The colour of ascetic fluid was yellow in majority of liver cirrhosis patients while it was Turbid in all malignant patients and Spontaneous Bacterial Peritonitis patients. In patients of Anemia- Hypoproteinemia, the colour was yellow in majority of patients. The ascitic fluid was transudate in nature in in majority of liver cirrhosis patients while it was exudate in all patients of Malignancy and Spontaneous Bacterial Peritonitis patients. Conclusion: The effectiveness of this approach is contingent upon standardization of techniques, comprehensive integration with clinical and biochemical data, and addressing variability and potential biases. While the findings offer promising implications for improved patient management and targeted treatment strategies, ongoing research and refinement are essential to fully realize the benefits and address the limitations observed in this study.